The Belgian Photonovel, 1954-1985 An Introduction - Colangelo, Clarissa (Studies in European Comics and Graphic Novels, 2023)
The importance of the Belgian contribution to the history of the photonovel. The Belgian photonovel is the missing link in the amazing history of the photonovel, a comics-inspired form of visual narrative that combines elements from very different genres and media, ranging from literary melodrama, cinema, and of course comics. This monograph discloses the specific Belgian contribution to the genre, in close connection with the singularities of the Belgian women's and general magazines where these photonovels appeared. If the photonovel is generally considered a typically French or Italian genre, this study demonstrates the importance of a different tradition, which appropriated the foreign models in a very original way. Belgian photonovels are distinct, not only because they tell other kinds of stories, but also because they interact with other types of magazines in ways that are very different from the mainstream forms of the genre in Italy and France. Finally, this lavishly illustrated study is also the first in scrutinizing the technical aspects of magazine printing techniques in the development of the photonovel. Ebook available in Open Access. This publication is GPRC-labeled (Guaranteed Peer-Reviewed Content).